Man, Land, and Water: Settlement Distribution and the Development of Irrigation Agriculture in the Upper Rud-i Gushk Drainage, Southeastern Iran - Prickett, Martha Ellen (1986)
Ph.D. Dissertation; 3 vols.; Order No. DA8704384; DissAbstr 47/11 (May 1984) 4120-A/4121-A.